The use of X-ray to evaluate Brachiaria brizantha seeds quality during seed processing - Jeromini, Tatiane; Martins, Cibele; Pereira, Francisco Elder; Gomes Júnior, Francisco (Revista Ciência Agronômica, 2019)
The X-ray test permits the visualization of the internal structures of seeds in a non-destructive way making thus possible the diagnosis of causes of seed low germination and purity. The objective of this project was to evaluate the quality of Brachiaria brizantha seeds by means of the X-ray test and the effect of the processing stage. The seeds were sampled before processing and after going through the air and screen machine, and the first and the second gravity tables. Seeds were evaluated as to water content, purity, weight of a thousand seeds, germination, and the X-ray test. The treatment replications were distributed according to a complete random design with four replications. The X-ray test permit to verify the completely full seeds as well as deteriorated, hollow, mechanically damaged seeds and empty spikelets. The processing procedure caused no damage to the seeds. The analysis by means of X-ray is a quality control procedure resulting in information that can be used in the adjustments of processing machines.